(untitled) (ASEAN Engineering Journal, 2025)
Bio-coagulants are attracting current research interest because they are more environmentally friendly and safer than traditional chemical coagulants. However, the main challenge for bio-coagulants is the production in bulk quantities at a reasonable cost. The main purpose of this study was to investigate the ability of Phanerochaete concrescens to produce an effective bio-coagulant in powder form. The one-factor-at-a-time approach (OFAT) was performed to evaluate the capacity of the powdered myco-coagulant for various initial turbidities and coagulant doses. The morphological structure, functional groups and crystallinity of the bio-coagulant were evaluated using scanning electron microscope (SEM), Fourier transform infrared (FTIR) and X-ray diffractometry (XRD), respectively. The addition of 0.09-0.11 g of powder myco-coagulant led to the maximum elimination of turbidity from synthetic kaolin wastewater, which was 80 % from an initial turbidity value of 750±10 NTU. SEM revealed that the fungus that produced the coagulant has a filamentous and linked network structure. FTIR illustrated the presence of hydroxyl, carbonyl, carboxyl, methoxyl and amino groups. The XRD analysis revealed the bio-coagulant to have smaller particle sizes with wider peaks. Based on the findings, Phanerochaete concrescens may find use in industry as a producer of powder bio-coagulants.